Administration of Dexmedetomidine inhibited NLRP3 inflammasome and microglial cell activities in hippocampus of traumatic brain injury rats. Issue 5 (17th October 2018) - Zheng, Bin; Zhang, Shuncai; Ying, Yanlu; Guo, Xinying; Li, Hengchang; Xu, Lixin; Ruan, Xiangcai
Abstract : The abnormally high nucleotide-binding oligomerization domain (NOD)-like receptor family pyrin domain containing 3 (NLRP3) inflammasome activity is a typical characteristic of traumatic brain injury (TBI). Dexmedetomidine (Dex) is a highly selective α-2 adrenergic receptor agonist that inhibits the activation of NLRP3. Thus, it was hypothesized that Dex could attenuate TBI by inhibiting NLRP3 inflammasome activity in hippocampus. Rats were subjected to controlled cortical impact method to induce TBI, and treated with Dex. The effect of Dex treatment on the cognitive function, NLRP3 activity, and microglial activation in rat brain tissues was assessed. The administration of Dex improved performance of TBI rats in Morris water maze (MWM) test, which was associated with the increased neurone viability and suppressed microglia activity. Moreover, the administration of Dex inhibited the neuroinflammation in brain tissue as well as the expressions of NLRP3 and caspase-1. Additionally, Dex and NLRP3 inhibitor, BAY-11-7082 had a synergistic effect in inhibiting NLRP3/caspase-1 axis activity and improving TBI. The findings outlined in the current study indicated that the improvement effect of Dex on TBI was related to its effect on NLRP3 activity.